PENENTUAN PARAMETER OKSIDASI MINYAK BUAH MERAH (Pandanus conoideus, Lam) SECARA SPEKTROFOTOMETRI INFRAMERAH DAN KEMOMETRIKA - , LISA ANDINA ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Oil and fat oxidation is one of most important factor that can affect shelf life and nutrition value of oil. Red fruit oil (RFO) is a rapidly growing commodities market at a price which is comparatively higher than other oils.This Study was conducted to develop infrared spectrophotometry combined with multivariate calibration of partial least square for determination of peroxide value and p-anisidine value of red fruit oil. Red Fruit Oil was obtained through maceration process of red fruit with methanol, followed by the partition using n-hexane and chloroform to obtain hexane and chloroform fractionsof RFO. Both fractions of RFO then added with antioxidant BHT and Î±-tocopherol of 200 mg.Kg-1respectively, and heated at a temperature of 100, 150, 180, 200, and 300 0C. These RFOsare further subjected to determination of peroxide value and p-anisidine value usingtitrimetric method and ATR-FTIR spectrophotometry with chemometric multivariate calibration. Based on the optimization processes to select a wavenumber of RFOâs FTIR spectra, it can be shownthat ATR-FTIR method combined with PLS can be used for determination of peroxide value at 3085-3610 cm-1 withR2 for the relationship between the actual peroxide value determined by titrimetric method and the value predicted by FTIR spectrophotometry of 0.997, and standard error calibration of 0.14% (v/v)